Análise e avaliação de materiais informativos disponíveis na web para pais sobre os transtornos específicos da aprendizagem - Karina de Almeida Marques (2017)
Once entering the school universe even typical children may prove difficulties or delays in the reading, writing and arithmetic´s learning. In some circumstances, these difficulties become persistent; countless parents might experience feelings of guilt, fear, and helplessness, which often lead them to postpone the search for help. Nevertheless, when this quest becomes unsustainable, the parents face questions like what to do and where to find guidance. Nowadays, more and more people are appealing to the web. Thus, to know what is available in this space, we investigate Trends, sites and materials (booklets/guides, videos, and articles) on learning difficulties, focusing on Specific Learning Disorders. After a survey of the keywords used by non-specialist to search for such disorders, we found via Google, Bing, Qwant and Yandex 69 sites and five booklets and a children's book. Via YouTube (through the "snowball" methodology), we selected 11 videos; and via Google Scholar and Biblioteca Virtual de Saúde (BVS, Virtual Health Library in english) 20 articles (10 first options from each search results page). The data were analyzed IRAMUTEQ linguistic and RStudio statistical software. Besides, they were evaluated through an exhaustive assessment of the content, graphical resources and by a judge [The methodology was descriptive quantitative and exploratory with a crosssectional design]. The results indicate that the keywords used by laypeople to search for information on the Internet are different from the indexes used by academics to publish them. The top sites Suggested by the popular search engines are Wikipedia and private pages. Articles and booklets are not among the most common options, being difficult to find quality and deep information. The format of preference is the audiovisual style. There are few materials on the web, and access to up-to-date and in-depth information is difficult. The analysis of the contents indicates the existence of three main categories of information. Lexicogrammar resources of formality and communication, the format of the text are the first. Theoretical approach (conceptualization and causes), the second and practical approach (recommendations and consequences) the third. It was observed the existence of a continuum initiated by informal, accessible, dialogic and multimodal language, endowed with generic learning content (represented by TV program videos) and finalized in a formal, technical, specific, monological and resource-limited language multimodal (represented by the articles). The booklets are located closer to the scientific reports than to the videos, in a position that stands out for the adoption of language now of guidance or explanation. It is concluded that scientific dissemination should entail four main elements: ensuring access to the population (adequate choice of keywords, publication in relevant sites), clarity of the language adopted (explaining in depth, but adopting everyday terms), use of practical examples and the presence of multimodal resources that add compression to the product. With this research, we take the first step in the connection between teaching, research, and extension since the experience learned will direct the elaboration of new resources to overcome the misinformation and reduce the diagnostic journey's challenges